2016
DOI: 10.1039/c6ra02480g
|View full text |Cite
|
Sign up to set email alerts
|

Surface-modified spherical activated carbon for high carbon loading and its desalting performance in flow-electrode capacitive deionization

Abstract: We fabricated surface modified activated carbons covered with ion-selective polymer. These materials can be used as powerful dispersants and flow electrodes, and improved desalting efficiency by high carbon loading via electrostatic repulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…Many studies have demonstrated that carbon-based materials can meet the requirements of high performance CDI electrodes, such as activated carbon, porous carbon, carbon nanotubes, graphene and their composites with inorganic materials. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, almost all carbon-based materials for CDI electrodes reported to date are exclusively synthesized by using petroleum-derived chemicals, undoubtedly enhancing the cost of large-scale production applications. Therefore, seeking low-cost and abundant carbon sources to fabricate carbon-based materials for high-performance CDI is still highly requested.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that carbon-based materials can meet the requirements of high performance CDI electrodes, such as activated carbon, porous carbon, carbon nanotubes, graphene and their composites with inorganic materials. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, almost all carbon-based materials for CDI electrodes reported to date are exclusively synthesized by using petroleum-derived chemicals, undoubtedly enhancing the cost of large-scale production applications. Therefore, seeking low-cost and abundant carbon sources to fabricate carbon-based materials for high-performance CDI is still highly requested.…”
Section: Introductionmentioning
confidence: 99%
“…Another use of IEP coating is to act as a dispersant for carbons used in flow electrodes. As studied by Park et al ., activated carbon loading cannot be too high for flow electrodes because of its effect on the viscosity [110] . After coating AC with a polymer containing trimethylammonium (AC−N) and sulfonate (AC−S) groups, a lower viscosity was observed (Figure 6c–d) and higher AC loading became possible.…”
Section: Development Of Carbon‐based CDI Electrodesmentioning
confidence: 99%
“…By modifying cell architecture, only 35 wt. % carbon content of the slurry has been achieved so far [90]. Exploitation of carbon particles of low size (2-10 µm) and spherical carbons as application in slurry electrodes has also been reported thus enabling higher carbon loading and viscosity reduction.…”
Section: Flow Capacitive Deionization (Fcdi)mentioning
confidence: 99%